Minimally invasive aesthetic procedure for discolored teeth: Prosedur estetik minimal invasif pada gigi yang mengalami diskolorasi - Sari Arianti Ali; Nurhayaty Natsir (Makassar Dental Journal, 2024)
This case report is aimed to describe the case management of a 20-year-old woman who came to Unhas RSGMP with the main complaint of yellowish upper and lower front teeth due to frequent consumption of tea for a long time. The patient felt less confi-dent and wanted her teeth to be whiter. The stages of external bleach treatment are carried out, namely tooth cleaning using a brush and pumice then determining the initial colour of the patient's teeth using the opalescence boost shade guide, astringent ap-plication to the gingival sulcus then gingival barrier. H2O2 40% bleach material was applied for 20 minutes with 2 application cy-cles. In the final stage, application of desensitiser material and giving post-bleaching instructions to the patient. After the bleach procedure, there was an increase in tooth colour of 4 grades from A2 to B1. At the 8-day post-bleaching control, there was no change in tooth colour. The patient was satisfied with the treatment results. It is concluded that external bleaching is a minimally invasive treatment that is simple and effective in providing aesthetic results on teeth that have extrinsic discoloration.